Answer:
Step-by-step explanation:
I suspect it is 64 not 65,
9x^2-64y^2
= (3x - 8y)(3x + 8y).
(If it is 65 there are no factors)
Answer:
x³ + 5x² + 5x - 2
Step-by-step explanation:
Given
x³ + 3x² - x + 2x² + 6x - 2 ← collect like terms
= x³ + (3x² + 2x² ) + (- x + 6x ) - 2
= x³ + 5x² + 5x - 2
15 is the awnser too this one
Answer:
Step-by-step explanation: A function y=(x-10)(x-2) will have its zeros at x=10 and x=2. y=x²-12x+20.
Step-by-step explanation:
Y-int, x=0
y = 2(0) therefore y-int is (0,0)
x-int, y=0
0=2x
x = 0 therefore x-int is (0,0)